Magnetic Resonance Imaging (MRI) Lumbosacral Spine Findings in Patients With Low Backache: A Clinico-Radiological Relation - Ehsan, Jovaria; Majeed, Ayesha Isani; Haq, M Ehsan ul; Riaz, Ramish; Ehsan, Momna (Pakistan Armed Forces Medical Journal, 2023)
Objective: To correspond clinical findings of patients with lower backache to those demonstrated at Magnetic Resonance Imaging of the Lumbosacral spine. Study Design: Cross-sectional study. Place and Duration of Study: Department of Diagnostic Radiology, Pakistan Institute of Medical Sciences Hospital, Islamabad Pakistan, from Oct 2019 to Jan 2020. Methodology: All consecutive adult patients with lower backaches of more than one month duration were enrolled in the study. Detailed clinical history and examination were obtained. Pain scoring was done by visual analogue score, and a straight leg raise test was performed. Patients then underwent magnetic resonance imaging in the hospital, and findings were reported. Results: Mean age of the patients was 30.2±13.53 with male preponderance. The mean duration of symptoms was 2.3±2.34 years. According to the visual analogue score, most patients had a moderate pain scale. Seventy-six percent of patients had no sensory deficit; upon clinical examination, twenty-one had a loss of power. Upon Lasegue Test, the majority (43,48.9%), had pain between 30-70 of hip flexion. Conclusion: History and detailed clinical examination play an emphasising role in the treatment regimen of patients with lower backache, with special concern on the correlation of findings with Magnetic Resonance Imaging of the lumbosacral spine, thus alleviating morbidity of patients.